Validation to Spanish of the Caring Assessment Tool (CAT-V) - Rosa María Fernández Ayuso; Juan Manuel Morillo Velázquez; David Fernández Ayuso; Julio César de la Torre-Montero (Universidade de São Paulo, 2017)
Resume Objective: to translate and validate to Spanish the Caring Assessment Scale tool, CAT-V, by Joanne Duffy, within the framework of Jean Watson; as a secondary objective, it is proposed to evaluate its psychometric properties. There are tools designed to measure the patient's perception of provided cares, including CAT-V, the subject of our interest, in a way that it can be used in Spanish-speaking patients. Methods: to meet the objectives, it was performed sequential translation and retro-translation of the scale to be validated, through a standardized procedure. The final version of that scale was validated in a sample of 349 patients from four public and two private hospitals in Madrid, Spain. Results: The instrument was translated and validated with high internal consistency (Cronbach's alpha .953). The subsequent factor analysis revealed a three-factor structure, not coincident with the data from the US population. Conclusion: it is considered that the translation of CAT-V is a suitable instrument to be used in the evaluation of patient care in Ibero-american health centers whose language is Spanish.